Courtly love songs of medieval France : transmission and style in the trouvère repertoire - O'Neill, Mary J. (Oxford Monographs on Music Ser., 2006)
Mary O'Neill examines the legacy of the medieval poet composers of Northern France, the trouvères. For many years problems and difficulties concerning the surviving melodies have prevented us from accessing these songs. Many of these problems are addressed here, bringing us closer to a true understanding of the repertoire. - ;This book is the first full-length study of the courtly love songs of the trouvères to address the central musical problems of the repertoire as a whole, embracing source studies, interpretation, historiography, and analysis.